Efeito do carregamento mecânico no torque de remoção de dois diferentes tipos de pilares para implantes com conexão cone morse - Pintinha, Marilene (2011)
Statement of problem: The mechanical behavior of different types of morse-taper abutments for cemented prosthesis is not completely known. Purpose of study: Assess the effects of simulated mechanical loading on the removal torque of two designs of morse-taper abutments. Material and methods: Forty-eight assemblies abutment/implant divided into two groups of 24 were used: group 1, solid abutment (one piece), and group 2, esthetic abutment (two pieces). Each group was subdivided into A (control) and B (test) without and with mechanical loading, respectively. For groups 1A and 2A, the abutments were removed and removal torque values (RTVs) registered. The same was done for groups 1B and 2B, after mechanical loading (500,000 cycles). Groups 2A and 2B were further tested for traction. For data analysis Student's t-test was used, at 95% level of significance. Results: All abutments tested presented lower RTVs when compared to installation torque. A statistically significant difference (p = 0,0016) was found when groups 1A and 1B mean results were compared, while no statistical differences (p = 0,3619) between groups 2A and 2B were found. For the traction test, however, a statically significant difference (p < 0,0001) between groups 2A and 2B was found. Conclusions: Cold welding did not take place in any of the solid abutment specimens. Even after the mechanical loading, esthetic abutments presented similar RTVs. After mechanical loading, the traction force necessary to remove the abutment from inside the implant presented a two-fold increase. Clinical implications: The morse-taper design has proven to be highly efficient the stability of the connection abutment/implant even under heavy off-center occlusal loads. The choice for one type of abutment over another must always be based on clear scientific evidence. In case of clinical need, solid abutments may be removed more easily and predictably than esthetic abutments with a separate screw, which, due to the nature of its design, may present some difficulties when being removed.